A influência do desbalanço superóxido- peróxido de hidrogênio na resposta à quimioterapia de células de câncer colorretal (HT-29): estudo in vitro - Azzolin, Verônica Farina (2016)
Introduction: manganese dependent superoxide dismutase (SOD2), is an important antioxidant enzyme, superoxide dismutase to anion produced in mitochondria in hydrogen peroxide, which in turn is catalyzed by glutathione peroxidase (GPX) into water and oxygen. Although be crucial for healthy cell, the role of SOD2 in cancer is highly controversial because in some kinds of cancers this enzyme exhibits a marked antitumor activity, while in others have a pro-tumor role. Previous investigations involving a polymorphism in codon 16 of SOD2 gene in which there is an exchange of a valine with an alanine (Val16Ala-SOD2) have associated increased efficiency of enzyme SOD2 at high risk of some cancers. However, in certain types of tumors, such as colorectal cancer are conflicting results. Studies suggest that high levels in tumor cells SOD2 colorectal cancers are associated with tumor progression. Perhaps this difficulty in defining the role of SOD2 in colorectal cancer biology is linked to great influence of environmental factors on the gastrointestinal system, especially the diet. For this reason, the development of an unbalance pharmacological model to investigate the role of superoxide-anion imbalance hydrogen peroxide (Superoxide Anion Hydrogen Peroxide imbalance, AS-HP) in colorectal cancer may be relevant. Objective: This study investigated the in vitro effect of drug-AS-HP imbalance caused by exposure to paraquat and the porphyrin in the viability and proliferative rate of commercial line of colorectal cancer cells (HT-29) and the response of these cells to chemotherapy oxaliplatin. The study also assessed the effect of AS-HP unbalance in the modulation of the expression of apoptotic genes, cell cycle and oxidative in HT-29 cells. Methods. HT- 29 obtained from American Type Cell Culture Collection (ATCC) were grown in DMEM, 10% fetal bovine serum, 1% antibiotic and antifungal in an oven with 5% CO2 and 37 ° C temperature. After 24 h the transfer of cells to 96-well plates at a concentration of 10 5 cells per well were exposed to these concentrations of 0.1 uM paraquat which is a superoxide-generating molecule or porphyrin which is a molecule with a similar effect SOD2 enzyme. Part of the cells was treated with oxaliplatin at a concentration of 20um and the other not. The effect on the viability, cell proliferation, cell cycle, apoptosis and modulation of genes of the cell cycle, apoptosis and oxidative metabolism (SOD1, SOD2, CAT, GPX, Caspase 3, Caspase 8, BAX, BCL-2 and P53colocar the name gene) was also evaluated. Assays were done in triplicate and compared by analysis of variance followed via test post hoc Tukey. Results: pharmacological imbalance AS-HP obtained via exposure of colorectal cancer cells to paraquat and porphyrin changed the standard of viability, cell cycle and in the modulation of gene expression. Both paraquat as nna porphyrin concentration 0.1 uM reduced the viability and proliferation rate of HT-29 cells. However, this effect was more pronounced in cells exposed to paraquat. The action of oxaliplatin was enhanced by the presence of paraquat when analyzed, the mortality rate, apoptosis, cell proliferation rate. Paraquat tamém induced cell cycle interruption phases S and G2 / M Any paraquat as porphyrin were able to modulate differentially markers of oxidative metabolism and expression of genes investigated. However, the results were quite heterogeneous. This heterogeneity may be associated with chromosomal instability in cancer cells that have high levels, and varied mutational. Conclusion: The results confirm the hypothesis that the AS-HP unbalance acts on the biology of colorectal cancer, and in particular increased levels of superoxide, not only increase the mortality rate but also inhibit cell proliferation enhancing so antitumor action of oxaliplatin. These results may be clinically relevant in the construction of pharmaceutical and / or nutritional strategies as the use of vitamins and other dietary supplements which operate in AS-HP sheet and to assist in the successful chemotherapeutic treatment of disease.